Dynamic Assessment of Agricultural Drought Risk in Qinghai-Tibet Plateau from 2000 to 2018 - LIU Guonie; LIANG Yuanyuan; QIU Yue; XIA Jingxia; DING Mengyao; SUN Peng (Renmin Zhujiang)
In the context of global warming and climate change,drought poses a serious threat to agricultural production.The Qinghai-Tibet Plateau is a “sensor” and “sensitive area” of climate change.Researching the agricultural drought risk of the Qinghai-Tibet Plateau is conducive to drought prevention planning of the area and improving the ability to resist drought.A risk assessment model is developed for agricultural droughts on the Qinghai-Tibet Plateau in light of regional disaster system theory,which is employed to investigate the hazard,exposure,vulnerability and spatiotemporal features of agricultural droughts therein.Moreover,the paper regionalizes the risk grade at a county level.The results show the followings:① The hazard of agricultural drought risk on the Qinghai-Tibet Plateau presents a “high-low-high” distribution from southeast to northwest,and the southeastern region shows an increasing trend.Wheat and highland barley in the eastern and southeastern Qinghai-Tibet Plateau are at a high agricultural drought risk from July to September.Forages in the northern region are at a high agricultural drought risk from April to August.② The regional difference of agricultural drought exposure in Tibet Plateau is small.The exposure shows an increasing trend in the east and northwest while a decreasing trend in the central and west.③ The agricultural drought vulnerability of 98.79% of the counties and cities is decreasing,which passes the significance test at the confidence level of 99%.④ The southeastern and northern regions of the Qinghai-Tibet Plateau witness a high agricultural drought risk and an increasing trend of it.